Constructing Ru/TiO2 Heteronanostructures Toward Enhanced Photocatalytic Water Splitting via a RuO2/TiO2 Heterojunction and Ru/TiO2 Schottky Junction. Issue 4 (15th December 2015) - Gu, Quan; Gao, Ziwei; Yu, Sijia; Xue, Can
Abstract : Photocatalysts based on metallic Ru and RuO2 dual co‐catalysts modified TiO2 nanobelts (NBs) are constructed through a wet‐impregnation reduction method with post thermal oxidation. The samples are characterized carefully and their photocatalytic activities for the half reactions of water splitting as well as full water splitting are evaluated systematically under solar light irradiation. The detailed characterizations and analyses clearly reveal the formation of a Schottky junction at the Ru‐TiO2 interface and of RuO2 /TiO2 heterojunctions. The results of the photocatalytic tests show that both Ru and RuO2 can improve the photocatalytic activity for H2 /O2 evolution and water splitting. Moreover, the photocatalytic activity of the TiO2 NBs can be further enhanced by co‐modification with dual Ru and RuO2 co‐catalysts. The RuO2 /TiO2 heterojunction improves the transfer of the photogenerated holes from the TiO2 to the RuO2, where water can be oxidized by the holes to evolve O2, and the Ru/TiO2 Schottky junction promotes the transfer of photogenerated electrons from the TiO2 NBs to the metallic Ru for proton reduction into H2 . These two processes are involved in the overall water splitting. This work provides an important reference for designing highly efficient photocatalysts for water splitting through loading of dual co‐catalysts containing the same element but with different valence structures. Abstract : The coexistence of RuO2 and Ru on TiO2 NBs leads to double‐junctions of Ru/TiO2 /RuO2 . Upon excitation of TiO2, the built‐in electric field in the double‐junction region promotes the separate transport of the photogenerated electrons and holes across the Ru/TiO2 Schottky junction and RuO2 /TiO2 heterojunction to Ru and RuO2 for proton reduction and water oxidation, respectively, thus achieving enhanced photocatalytic activities.